2021
DOI: 10.1007/s00296-021-04818-2
|View full text |Cite
|
Sign up to set email alerts
|

Use of conventional synthetic and biologic disease-modifying anti-rheumatic drugs in patients with rheumatic diseases contracting COVID-19: a single-center experience

Abstract: To examine whether patients with inflammatory arthritis (IA) treated with conventional synthetic (cs) disease-modifying anti-rheumatic drugs (DMARDs) and/or biologic (b) DMARDs, could be affected from SARS-CoV-2 infection and to explore the COVID-19 disease course and outcome in this population. This is a prospective observational study. During the period February–December 2020, 443 patients with IA who were followed-up in the outpatient arthritis clinic were investigated. All patients were receiving cs and/or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 40 publications
(33 reference statements)
1
12
0
Order By: Relevance
“…However, in the last year biological therapies and colchicine have been used as potential therapeutic agents against the SARS-CoV-2 infection [ 4 , 8 , 9 , 17 ]. Indeed, in patients with ARD who contracted COVID-19 whilst receiving biological therapies (especially cytokine inhibitors), the disease expressed with mild systemic manifestations, less hospitalization, and less severe complications [ 23 25 ]. On the other hand, in patients with FMF or gouty arthritis receiving colchicine, the disease manifested without severe respiratory complications and they recovered without additional treatment [ 26 28 ].…”
Section: Colchicine and Covid-19mentioning
confidence: 99%
“…However, in the last year biological therapies and colchicine have been used as potential therapeutic agents against the SARS-CoV-2 infection [ 4 , 8 , 9 , 17 ]. Indeed, in patients with ARD who contracted COVID-19 whilst receiving biological therapies (especially cytokine inhibitors), the disease expressed with mild systemic manifestations, less hospitalization, and less severe complications [ 23 25 ]. On the other hand, in patients with FMF or gouty arthritis receiving colchicine, the disease manifested without severe respiratory complications and they recovered without additional treatment [ 26 28 ].…”
Section: Colchicine and Covid-19mentioning
confidence: 99%
“…The results of previous studies [18][19][20]25] showed the positive effects of anti-TNF drugs on reducing the severity of COVID-19 and hospitalization percentage. Moreover, our results indicated the effect of TNF-a inhibitors in decreasing the incidence of COVID-19.…”
Section: Discussionmentioning
confidence: 94%
“…For example, it was reported that the severity of COVID19 symptoms and the need for hospitalization were lower in patients with inflammatory bowel disease (IBD) who were receiving anti-TNF treatments [18]. In another study, no correlation between consumption of TNF-a blockers and increased severity of COVID-19 in patients with rheumatic diseases has been observed [19]. Moreover, the results obtained from data of the COVID-19 Global Rheumatology Alliance registry indicated that anti-TNF decreased the chance of hospitalization caused by COVID-19 in patients suffering from rheumatic disease [20] and TNF inhibitors are not associated with death caused by COVID-19 [21].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the COVID‐19 status of the studied populations, we analysed studies that reported the association between anti‐TNF treatment and the risk for hospitalisation, ICU admission and death due to COVID‐19 in patients with COVID‐19 17,67,76‐85,68,86‐94,69‐75 and in patients who receive anti‐TNF treatment without having contracted SARS‐CoV‐2, 95‐101 separately.…”
Section: Resultsmentioning
confidence: 99%